Politics of tax law in supporting the progress of the digital economy - Hasiholan, Samuel (Institute Of computer Science (IOCS), 2025)
This research explores Indonesia's tax collection system, which operates on a self-assessment basis, relying on taxpayers' trust and responsibility to calculate, deposit, and report their taxes. With the rapid growth of the digital economy, regulatory gaps may arise, potentially leading to under-collection of taxes and affecting state revenue. The main issue addressed is whether current tax policies adequately support the advancement of the digital economy. The study employs normative juridical research, analyzing legal materials such as laws, regulations, and societal norms related to taxation. The findings indicate that some tax policies aim to facilitate the digital sector, including tax incentives for startups and micro, small, and medium enterprises (MSMEs). These incentives are intended to stimulate innovation and growth within the digital ecosystem. However, their implementation and effectiveness require periodic evaluation. The conclusion emphasizes that tax collection must adhere strictly to existing laws, ensuring that levies intended for state purposes are regulated legally. The study also recommends ongoing socialization efforts about e-commerce tax regulations, particularly whenever updates occur, not only for MSMEs utilizing marketplaces but also for cross-border e-commerce actors. Engaging relevant stakeholders, especially the Ministry of Finance, is crucial to ensure compliance and maximize revenue from the expanding digital economy